An Analysis of Autopsy-Radiology Discordance in Cases of Fatal Blunt Force Injury - Natalie L., Adolphi; Grace Wong, Yi-Li; Jamie, Elifritz (2024)
Learning Overview: After attending this presentation, attendees will learn about the interpretation of Postmortem Computed Tomography (PMCT) in cases of fatal blunt trauma.